Short‐term Detection of Imidacloprid in Streams after Applications in Forests. Issue 3 (1st May 2018) - Wiggins, Greg; Benton, Elizabeth; Grant, Jerome; Kerr, Marie; Lambdin, Paris
Abstract : Imidacloprid, a neonicotinoid insecticide, is a major component of hemlock woolly adelgid (HWA) [ Adelges tsugae (Annand)] management programs that are critical to protecting forest health in the eastern United States. However, the impact of imidacloprid soil applications in forests on some aquatic macroinvertebrate species by leaching into aquatic systems is uncertain. The time for residues from imidacloprid soil applications to migrate from treated hemlocks to nearby streams and the concentrations at which imidacloprid may occur after initial migration is unknown. The presence and concentration of imidacloprid in three streams adjacent to recently treated hemlock (soil drench >10 m from stream channels) were assessed in the Big South Fork National River and Recreation Area. Two standard water grabs were collected monthly for 1 yr from a location downstream from imidacloprid‐treated areas. Samples were analyzed using liquid chromatography tandem mass spectrometry (limit of detection = 0.025 μg L −1 ). Imidacloprid was detected in all treatment streams during a single rain event that occurred 184 to 196 d after treatments, and concentrations ranged from 0.053 to 0.833 μg L −1 . Imidacloprid was not detected on any other sampling date from treatment streams. All observed positive detections exceeded the USEPA freshwater invertebrate chronic endpoint (0.01 μg L −1 ). One stream sample exceeded the USEPA freshwater invertebrate acute endpoint (0.39 μg L −1 ). However, previous macroinvertebrate community assessments in streams with similar concentrations did not indicate negative effects to aquatic fauna. These findings help characterize the risk of imidacloprid treatments to stream macroinvertebrates within 1 yr of soil applications. Core Ideas: Short‐term movement of imidacloprid from treated forest trees to streams was unclear. Imidacloprid was detected in all three treatment streams ≥184 d after treatment. Imidacloprid concentrations in streams ranged from 0.053 to 0.833 μg L −1 . Some concentrations were above USEPA freshwater invertebrate chronic and acute endpoints.